Centrosymmetric to noncentrosymmetric structural transformation of new quaternary selenides induced by isolated dimeric [Sn2Se4] units: from Ba8Ga2Sn7Se18 to Ba10Ga2Sn9Se22. Issue 14 (23rd January 2017) - Li, Yan-Yan; Wang, Jin-Qiu; Liu, Peng-Fei; Lin, Hua; Chen, Ling; Wu, Li-Ming
Abstract : An interesting centrosymmetric to noncentrosymmetric structure transformation from Ba8 Ga2 Sn7 Se18 to Ba10 Ga2 Sn9 Se22 induced by isolated dimeric [Sn2 Se4 ] units was reported. Abstract : A noncentrosymmetric structure is a prerequisite of many important properties, such as ferroelectric, piezoelectric and nonlinear optical properties. The design synthesis of a noncentrosymmetric compound is highly desired but it is a great challenge. Herein, two new quaternary selenides, Ba8 Ga2 Sn7 Se18, 1 and Ba10 Ga2 Sn9 Se22, 2, have been discovered by solid-state reactions. Compound1 crystallizes in the centrosymmetric space group Pnma (no. 62) with a = 12.466 (9) Å, b = 9.358 (6) Å, c = 18.14 (2) Å, V = 2116 (3) Å 3, Z = 2; and2 crystallizes in the noncentrosymmetric space group Cmc 21 (no. 36) with a = 9.384 (2) Å, b = 44.834 (6) Å, c = 12.416 (2) Å, V = 5224 (2) Å 3, Z = 4. The major motif of both1 and2 is the [Ga2 Sn7 Se18 ]∞ 16− ladder chain built by alternately jointed GaSe4 tetrahedra and SnSe4 tetragonal pyramids, and to each of these polyhedra, an accessory (SnSe3 pyramid or Sn2 Se4 dimer) is attached. Interestingly, the noncentrosymmetric structure of2 is the combination of centrosymmetric1 and the imbedded isolated dimeric [Sn2 Se4 ] with a C 2v polar symmetry that separates every two such ladder chains.1 and2 directly illustrate that a simple combination reaction can drive the centrosymmetric to noncentrosymmetric structural transformation.